Moderate Proficiency in Suture Techniques Among Nurses: A Cross-Sectional Study - Husham Hussain Abdul -Ra’aoof; Sundus Baqer Dawood; Firas A Jassim; Saja Kareem Jassim; Sajjad Salim Issa; Ali Malik Tiryag; Mohamad A Akber; Maher Abdulameer Atiyah (Academia Open, 2024)
This study aimed to evaluate the knowledge of healthcare providers, specifically nurses, regarding suturing skills, methods, and types at Al-Basrah Teaching Hospital. A descriptive cross-sectional approach was adopted from January 1, 2023, to July 30, 2023. A purposive sample of 100 nurses, representing both genders and various wards, participated. Preliminary validation was conducted through a pilot study involving ten healthcare providers, and Cronbach's Alpha assessed the survey's reliability. Data analysis was executed using SPSS version 26, focusing on descriptive statistics (mean, SD, frequency) and inferential statistics (chi-square). The demographic profile showed an equal distribution in age (50% aged 20-35), a slight female predominance (52%), and a majority holding diplomas (56%). Results indicated a moderate level of knowledge and proficiency in suturing skills and techniques among the participants. These findings suggest a need for enhanced training and education in suturing to improve patient care outcomes in clinical settings. Highlights : Moderate Suturing Proficiency: Nurses displayed a medium level of knowledge and skill in suturing techniques. Demographic Diversity: Sample included a balanced age distribution, slight female predominance, and majority diploma holders. Training Implications: Results highlight the necessity for improved suturing education to enhance patient care quality. Keywords : Suturing Skills, Nurse Education, Healthcare Training, Cross-Sectional Study, Clinical Competency